Evolving Patterns in Inpatient Pediatric Consultations to Allergy/Immunology at an Academic Medical Center - Madeline Wurst; Anna Brameli; Matthew Krantz; R. Stokes Peebles, Jr; Yasmin Khan; Cosby A. Stone, Jr (University Library System, University of Pittsburgh, 2024)
Background: Consultations to pediatric allergy/immunology are of benefit to many hospitalized inpatients, but there is limited current information about how T-cell receptor excision circles (TREC) screening may have changed these patterns for pediatric populations. We aimed to determine the types of consults being requested and their relative frequencies for primary pediatric allergy/immunology consults under an academic fellowship program since the start of TREC screening in 2016. Information gained could help identify focal concepts for pediatric allergy inpatient training curricula for fellowship and graduate medical education programs.  Methods: Under an IRB approved study of an academic allergy fellowship consultation log, we retrospectively reviewed electronic medical records of pediatric allergy and immunology consults and categorized consultations by their primary indication.    Results: Three-hundred and eighty-three pediatric allergy/immunology consultations were seen between September 4, 2016 to November 24, 2022.  In terms of frequency, the most common consultation was for immunodeficiency evaluation or treatment, n=205 (53.5%), followed by drug allergy n=55 (14.4%), general allergy concerns n=43 (11.2%), skin allergy n=35 (9.1%), and less commonly inflammatory syndromes, n=26 (6.8%) and food allergy, n=19 (5.0%).  Questions related to TREC screening comprised 21% of all immunodeficiency consults, at n=43. Conclusion: At an academic allergy center where all allergy/immunology service lines are currently provided, the most common reason for pediatric consultations were for help with immunodeficiency evaluation/treatment and drug allergy. TREC screening is a new key indication for consultation. Fellowship programs may benefit from focusing on these content areas for the pediatric inpatient setting.